Path Analysis on the Fad Diets and other Factors Affecting the Risk of Chronic Energy Deficiency among Adolescent Females at the Boarding School - Widhiyanti, Fitria; Dewi, Yulia Lanti Retno; Qadrijati, Isna (Masters Program in Public Health, Universitas Sebelas Maret, Indonesia, 2020)
Background: Chronic Energy Deficiency (CED) is a state of lack of energy and protein in